Golongan pemuda-pemudi dalam novel Tamil Malaysia, 1970- 2010: Kajian perwatakan Suri Teladan dan Devian / Annadurai Murogaiah - Annadurai, Murogaiah (2018)
This thesis is entitled 'The Youths in Malaysian Tamil Novels, 1970-2010: The Characterization of Exemplary Behavior and Deviance'. The objectives of this study are to identify the characteristics of exemplary and deviant behavior among youths in Malaysian Tamil novels, examines the identities of youths in the Malaysian Tamil novel and also analyzes the characterization of youths as bearers of the tradition, legacy and aspirations of the Tamil community. The methodology of this study is qualitative. A descriptive and analytical approach used was in this study. The library research were also used to collect the informations. Psychoanalysis theorist Sigmund Freud’s and Erik Erikson’s theories was used to analyze and discuss the texts and recognize the various characterizations. The study is divided into six chapters. Chapter one is the introductory chapter. The second chapter is a chapter on concepts and theory. Chapter three is a chapter that describes the history of Tamil novel development in Malaysia. Chapter four describes the characterization of exemplary youths in Malaysian Tamil novels. Chapter five discusses the characteristics of deviant youths. Chapter six is the concluding chapter. The overall findings show that the characteristics of the exemplary youths are uplifted and the behavior of deviant youths are shown as characteristics that need to be corrected. Exemplary characters are described as a youth group which has its own role and importance in the development of society and country. Exemplary youths are regarded as the current and future leaders who are required to move forward with maturity, high capacity, and motivation that is more positive and effective with stronger commitment. In addition, deviant youths are a group that needs to be observed and bettered. The Tamil community's hopes in exemplary characters are an inspiration to the generation of youths who are the bearers of tradition, heritage, and aspirations of society. Meanwhile, deviant characters are youths who must be corrected and returned to reality. This is because the awareness of youths is very necessary in supporting the ideals of building a respected and dignified nation.